(untitled) (CIPEEX, 2025)
The Academic League for Wounds and Dressings (LACEF) actively participated in a community action in response to the increase in dengue cases, integrating into the UniEvangélica Itinerant Citizen Project - ImmunizACTION Health Education, in partnership with the Anápolis Municipal Government. The project, carried out in two municipal schools, aimed to expand vaccination coverage against dengue through educational activities, such as lectures and theatrical presentations, focused on children and adolescents aged 6 to 14. The involved academics were trained to transmit information in a playful and accessible way, aiming to raise awareness among the target audience and their guardians about prevention, symptoms, and the importance of immunization against dengue. The experience highlighted the crucial role of educational initiatives for the promotion of public health and emphasized the relevance of the participation of multidisciplinary academic leagues in projects that integrate education and health, with the objective of positively impacting the community and strengthening the culture of prevention and collective responsibility.